Աւանդական ժողովրդական տարազի մի տարբերակ (ըստ աղձնիքահայերի շրջանում պահպանուած նիւթերի) - Նահապետեան, Ռաֆիկ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье рассматривается народный традиционный костюм армянского населения исторической провинции Агдзник, который по сей день всесторонне не изучен. Данный атрибут соответствовал географическому местоположению, чрезвычайно разнообразным климатическим условиям, сложившимся феодальным взаимоотношениям, многовековым этническим традициям и предметам быта. Сравнивая имеющиеся материалы, можно увидеть, что часть народных костюмов Сасуна, краткое и неполное описание которых дает историк X века Товма Арцруни, сохранялась у армян Агдзника до геноцида и депатриации армян. В исследовании представлены традиционные компоненты одежды армян Сасунского, Багешского, Бшерикского районов и Сливанской долины, а также описан ряд элементов праздничного наряда. Отдельно описываются элементы мужского и женского костюма разных возрастных групп: одежда, головные уборы, обувь, украшения и т. д. Автор приходит к выводу, что в конце XIX века изменения армянского национального костюма городского населения были обусловлены значительными изменениями в социально-экономической жизни и влиянием городской моды. The article deals with the traditional folk costumes of the Armenian population of the historical province of Aghdznik, which has not been comprehensively studied to this day. This attribute corresponded to the geographical location, extremely diverse climatic conditions, established feudal relations, centuries-old ethnic traditions and household items. Comparing the available materials, it can be seen that some of the folk costumes of Sasun, a brief and incomplete description of which is given by the 10th century historian Tovma Artsruni, were preserved among the Armenians of Aghdznik until the genocide and depatriation of Armenians. The study presents traditional components of clothing of the Armenians of Sasun, Baghesh, Bsherik regions and the Slivan Valley, and also describes a number of elements of festive attire. The elements of men’s and women’s costumes of different age groups are described separately: clothing, headwear, footwear, jewelry, etc. The author concludes that at the end of the 19th century, changes in the Armenian folk costumes of the urban population were due to significant changes in socioeconomic life and the influence of urban fashion.
Keywords: Պատմութիւն; Ազգագրութիւն; Տարազներ